Incidence and clinical characteristics of inflammatory bowel disease in a developed region of Guangdong Province, China: A prospective population‐based study. Issue 7 (20th June 2013) - Zeng, Zhirong; Zhu, Zhenhua; Yang, Yuyu; Ruan, Weishan; Peng, Xiabiao; Su, Yuhuan; Peng, Lin; Chen, Jinquan; Yin, Quan; Zhao, Chao; Zhou, Haihua; Yuan, Shuai; et al.
Abstract Background and Aims The incidence of inflammatory bowel disease (IBD) is increasing in China with urbanization and socioeconomic development. There is however a lack of prospective, population‐based epidemiology study on IBD in China. The aim of the study is to define the incidence and clinical characteristics of IBD in a developed region of Guangdong Province in China. Methods A prospective, population‐based incidence study was conducted from July 2011 to June 2012 in Zhongshan, Guangdong, China. All newly diagnosed IBD cases in Zhongshan were included. Results In total, 48 new cases of IBD (17 Crohn's disease [CD]; 31 ulcerative colitis [UC]) were identified over a 1‐year period from July 2011. Age‐standardized incidence rates for IBD, UC, and CD were 3.14, 2.05, and 1.09 per 100 000 persons, respectively. The median age of UC was 38, and that of CD was 25. Terminal ileum involvement only (L1), isolated colonic disease (L2), and ileocolonic disease (L3) were reported in 24%, 6%, and 71% of patients with CD, respectively. Twenty‐four percent of patients had coexisting upper gastrointestinal disease (L4). Inflammatory (B1), stricturing (B2), and penetrating (B3) behavior were seen in 65%, 24%, and 12% of CD patients, respectively. Fifty‐nine percent of CD and 26% of UC patients had extra‐intestinal manifestations. Conclusions This is the first prospective, population‐based IBD epidemiological study in a developed region of China. The incidence of IBD is similar to that in Japan and Hong Kong but lower than that in South Korea and Western countries.